PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA: SYSTEMATIC LITERATURE REVIEW - Reni Hartanti; Neni Mariana; Rooselyna Ekawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study is a systematic literature review aimed at evaluating the effectiveness of the Realistic Mathematics Education (RME) approach in enhancing students' critical thinking skills. RME is a mathematics teaching approach that emphasizes the use of real and relevant contexts to facilitate the understanding of mathematical concepts. Through the analysis of various relevant studies, this research explores how RME can enrich students' learning experiences and promote the development of critical thinking skills. The literature review findings indicate that RME has significant potential in improving students' abilities in analysis, evaluation, and problem-solving. The implications of these findings underscore the importance of integrating real-world contexts in mathematics education to develop essential critical thinking skills in students. This article provides insights for educators and researchers on the application and benefits of RME in the context of mathematics education.